Use of Integrative Medicine Practices by Pregnant Women with Restless Legs Syndrome - Fulya Çağli; Mürüvvet Başer; Özlem Kaplan (Atatürk University, 2024)
Objective: To determine the use of integrative medicine practices in pregnant women with restless legs syndrome. Methods: This cross-sectional descriptive study was conducted in the perinatology service and outpatient clinic of a university hospital between 2 February-11 May 2022. The study included 148 pregnant women with restless legs syndrome who met the inclusion criteria. Data were collected using the Restless Legs Syndrome Diagnostic Criteria Questionnaire, the Restless Legs Syndrome Severity Rating Scale, a Personal Information Form, and an Integrative Medicine Use Form. Results: The pregnant women of the 61.4% were in their last trimester, and 75.7% had no information about restless legs syndrome. Symptoms started at an average of 20.29 ± 8.65 weeks of gestation and 81.1% of the pregnant women did not consult a physician. Of those who did consult a physician, 57.7% consulted a gynecologist and 81.0% were recommended vitamins/minerals as a treatment. For syndrome symptoms, 50.7% of pregnant women used integrative medicine practices. The four most commonly used methods were taking vitamins (55.9%), prayer (51.9%), brisk walking (45.2%) and massage (33.3%). There was no statistically significant difference between the use of integrative medicine practices and the severity of restless legs syndrome (P> .05). Conclusion: Restless legs syndrome is a condition that is not widely recognized by pregnant women. About half of pregnant women try to manage the condition by using integrative medical practices for syndrome. Nurses and other health professionals should provide information to pregnant women to raise awareness of the disease and provide effective treatment options.